(untitled) (Jurnal Pendidikan Fisika, 2019)
The general objective of the research was to provide a resolution of thinking for lectures who were lecturers of the courses so that they can convince students that the material in the history of physicswas understood easly when presented with the appropriate teaching materials and instructional media. As for the specific purpose of the study was to determine the response of students to instructional material History Of Physics Teaching Material (SERFIS YES) based graphical learning medium for students of physics education studies Unismuh Makassar. This type of research was categorized as research and development with research design refers to the development of the 4D model. The research will be condusted at the University of Muhammadiyah Makassar, South Sulawesi especially those in physics education studies program as FKIP Unismuh Makassar. As for the process of research and development of teaching material was done starting from the stage of defining, designing, validating, testing materials and analyzed descriptively qualitative indicators based on student responses that have been developed previously. The result showed that the development of teaching material was done by combining the material with graphic design into a teaching material like comic. It made the students interested in reading the history of the development of physics, so expect the achievement of learning outcomes course the history of physics can be achived to tha maximum. Keywords: Development of Teaching Material, Physics History is Not Sure (SERFIS YES), Graphic Learning Media Tujuan umum dari penelitian ini adalah memberikan resolusi pemikiran bagi para dosen pengampuh mata kuliah agar mampu meyakinkan mahasiswa bahwa materi pada mata kuliah sejarah fisika lebih mudah dipahami apabila disajikan dengan bahan ajar dan media pembelajaran yang tepat. Adapun tujuan khusus dalam penelitian ini adalah mengetahui respon mahasiswa terhadap bahan ajar Sejarah Fisika Yakin Enggak Sulit (SERFIS YES) berbasis media pembelajaran grafis bagi mahasiswa Program Studi Pendidikan Fisika Unismuh Makassar. Jenis penelitian ini dikategorikan sebagai penelitian dan pengembangan (research and development) dengan desain penelitian mengacu pada pengembangan model 4D. Penelitian ini akan dilaksanakan di Universitas Muhammadiyah Makassar Sulawesi Selatan terkhusus pada Prodi Pendidikan Fisika FKIP Unismuh Makassar. Adapun proses penelitian dan pengembangan bahan ajar yang dilakukan dimulai dari tahap pendefinisian, perancangan, validasi, hingga uji coba bahan ajar dan selanjutnya dianalisis secara deskriptif kualitatif berdasarkan indikator respon mahasiswayang telah dikembangkan sebelumnya. Hasil penelitian menunjukkan bahwa pengembangan bahan ajar dilakukan dengan mengkombinasikan materi dengan desaian grafis menjadi sebuah bahan ajar layaknya komik. Hal ini membuat mahasiswa tertarik untuk membaca sejarah perkembangan ilmu fisika, sehingga diharapkan pencapaian capaian pembelajaran mata kuliah sejarah fisika dapat tercapai secara maksimal Kata kunci: Pengembangan Bahan Ajar, Sejarah Fisika Yakin Enggak Sulit (SERFIS YES), Media Pembelajaran Grafis